Timelike-Ruled and Developable Surfaces in Minkowski 3-Space E13 - Mofarreh, Fatemah (Frontiers in Physics, 2022)
In this study, the timelike-ruled and developable surfaces are constructed in Minkowski 3-space E13. Using the E. Study map, we demonstrate that dual forms of timelike-ruled and developable surfaces can be obtained from the coordinates and first derivatives of the base curve at the dual hyperbolic unit sphere. This is proposed as a novel method for obtaining timelike-ruled and developable surfaces. Some examples have also been provided.